Making manslaughter process, punishment and restitution in Württemberg and Zurich, 1376-1700 - Pohl-Zucker, Susanne (Medieval law and its practice, 2017)
"In Making Manslaughter, Susanne Pohl-Zucker offers parallel studies that trace the legal settlement of homicide in the duchy of Württemberg and the imperial city of Zurich between 1376 and 1700. Killings committed by men during disputes were frequently resolved by extrajudicial agreements during the late Middle Ages. Around 1500, customary strategies of dispute settlement were integrated and modified within contexts of increasing legal centralization and, in Württemberg, negotiated with the growing influence of the ius commune. Legal practice was characterized by indeterminacy and openness: categories and procedures proved flexible, and judicial outcomes were produced by governmental policies aimed at the re-establishment of peace as well as by the strategies and goals of all disputants involved in a homicide case."